Health Record and Provided Services Recording among Centers Implementing Rural Family Physician and Insurance Program in Northern Provinces of Iran - Mohammad Javad Kabir; Nahid Jafari; Mohammad Nahimi Tabihi; Ebrahim Mikaniki; Hasan Ashrafian Amir; Seiyed Davoud Nasrollahpour Shirvani; Araslan Dadashi; Ghasem Oveis (Tehran University of Medical Sciences, 2015)
Background: One of the key duties of family physician is to form health records and provided recording services. This study conducted to form health records and aevaluate health records in family physician program in Northern Province of Iran. Materials and Methods: This cross-sectional study was carried out in second half  2011. 139 of centers implementing family physician program in three provinces of Golestan, Mazandaran and Gilan were selected using systematic random sampling, and assessed performance recording of all family physicians. A self- designed questionnaire was used which the validity and reliability of were confirmed. Data were analyzed by SPSS18 at the significant level of p<0.05. Results: Out of the 189 assessed family physicians, the profile of patients referred to the second level and its results were recorded in referral record forms by 43 physicians. Out of 1890 studied families, 1559 families had health record which had filled 892(57%) health record completely. Out of 5869 assessed family members, 4229 patients were examined periodically by their family physician at least once and 1919(46%) results filled entirely. during 559 were reported with health records, among which 892 were filled out completely. There was a significant difference between referral record rates to registered specialist between the Northern Province of Iran (P=0.001). Conclusion: The quantity and quality of health record formation was not in the expectation level as well and appropriate interventions are needed.